Дневник свекрови: [роман] / Мария Метлицкая - Метлицкая Мария (Эксмо, 2020)
Экземпляры: ф. 23 (20220303ԁ) / Инвентарный номер: 63118 / Цена: 130.00 / Авт.знак: М 54 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6